Prevalensi Hipertensi pada Aplikator Pestisida dan Faktor yang Berkontribusi: Studi Potong Lintang - Jen Fuk Liem; Apricylia Gloria Elizabeth Lumanauw; Yosephin Sri Sutanti; Johannes Hudyono (Jurnal MedScientiae, 2023)
The purpose of this study is to determine the prevalence of high blood pressure (HBP) and the contributing factors in pesticide applicators in Cibodas Village, where chemical pesticides are widely utilized. This cross-sectional study included 90 pesticide applicators in total. The information on individual and occupational characteristics was gathered using a structured interview-administered questionnaire. An upper-arm digital blood pressure monitor was used to measure blood pressure. Data were presented descriptively, and statistical analysis was performed using the chi-square and multiple logistic regression. The majority of participants were men. 94% of individuals used a combination of pesticides on a regular basis. In this study, the prevalence of HBP was 48.9%. High BP was associated with age > 44 years, and a high exposure group. These results support the idea of the importance of multisectoral collaboration in providing knowledge about the potential health effects of exposure to pesticides and comprehensive training on the proper handling of pesticides in agriculture.